Synthesis and Anticancer and Antiviral Activities of C-2'-Branched Arabinonucleosides - Bege, Miklós; Kiss, Alexandra; Bereczki, Ilona; Hodek, Jan; Polyák, Lenke; Szemán-Nagy, Gábor; Naesens, Lieve; Weber, Jan; Borbás, Anikó (International journal of molecular sciences, 2022)
d-Arabinofuranosyl-pyrimidine and -purine nucleoside analogues containing alkylthio-, acetylthio- or 1-thiosugar substituents at the C2' position were prepared from the corresponding 3',5'-O-silylene acetal-protected nucleoside 2'-exomethylenes by photoinitiated, radical-mediated hydrothiolation reactions. Although the stereochemical outcome of the hydrothiolation depended on the structure of both the thiol and the furanoside aglycone, in general, high d-arabino selectivity was obtained. The cytotoxic effect of the arabinonucleosides was studied on tumorous SCC (mouse squamous cell) and immortalized control HaCaT (human keratinocyte) cell lines by MTT assay. Three pyrimidine nucleosides containing C2'-butylsulfanylmethyl or -acetylthiomethyl groups showed promising cytotoxicity at low micromolar concentrations with good selectivity towards tumor cells. SAR analysis using a methyl β-d-arabinofuranoside reference compound showed that the silyl-protecting group, the nucleobase and the corresponding C2' substituent are crucial for the cell growth inhibitory activity. The effects of the three most active nucleoside analogues on parameters indicative of cytotoxicity, such as cell size, division time and cell generation time, were investigated by near-infrared live cell imaging, which showed that the 2'-acetylthiomethyluridine derivative induced the most significant functional and morphological changes. Some nucleoside analogues also exerted anti-SARS-CoV-2 and/or anti-HCoV-229E activity with low micromolar EC50 values; however, the antiviral activity was always accompanied by significant cytotoxicity.
Keywords: time-lapse imaging; thiosacharidy; coronavirus; SARS-CoV-2; anti-tumor; nucleoside analogue; antiviral; antivirové látky; COVID-19; Mice; Arabinonucleosides; arabinonukleosidy; Acetals; Nucleosides; zvířata; vztahy mezi strukturou a aktivitou; Humans; nukleosidy; Thiosugars; sulfhydrylové sloučeniny; pyrimidinové nukleosidy; Purines; puriny; myši; acetaly; photocatalytic thiol-ene reaction; Antiviral Agents; Structure-Activity Relationship; Sulfhydryl Compounds; Pyrimidine Nucleosides; lidé; Animals